Cyclic Universe Motion in Relativistic Radial Density Theory - Novakovic, Branko (European Journal of Applied Sciences, 2026)
In other to describe of the New Cyclic Cosmological Motion (NCCM) one can start with the Relativistic Radial Density Theory (RRDT). In this theory Planck’s and gravitational parameters can be described as the function of the mass density values. This density is maximal at the minimal gravitational radius and minimal at the maximal gravitational radius. These processes are functions of the radial density values (). For the description of the expansion and contraction of the mass objects one needs to know the related radial density value. These values can be described as the function of the mass (energy) constant, κ. Following the previous consideration here it is developed a new dynamics model of the universe motion. This model is the function of the minimal (not zero) radius (with maximal radial densityand of the maximal (not infinite) radius with the minimal radial density, .